Strategy For Increasing Income Of Rice Farmers In Labuhan Batu District - Ade Firmansyah Tanjung (JASc (Journal of Agribusiness Sciences), 2020)
Farmers have not been able to achieve income values that are in line with minimum wage standards. The purpose of this study is to calculate the amount of income of rice farmers in the study area. Identifying internal and external factors that affect income based on observations and interviews in the study area, in order to determine what strategies are appropriate for increasing the income of rice farmers in the study area. The analysis method used in this study uses the SWOT analysis method. The results of the study were obtained: 1). The average amount of income from the total number of paddy rice farmers in the study area is Rp.6,607,911 / planting season, with an average amount of production of 2,936 kg / planting season. 2). The results of the identification of factors that become the strength of farmers in the field consist of farmer motivation, farmer experience, suitability of paddy fields, level of technology adoption. 3). The results of the identification of factors that become farmers' weaknesses in the field consist of lack of capital, use of fertilizer that is less than the maximum, wide land area that is still narrow, the dynamics of farmer groups. 4). The results of the identification of factors that provide opportunities for farmers in the field consist of access to credit, ease of availability of seeds and fertilizer, availability of means of production assistance, government support in the construction of salt water fortifications. 5). The results of the identification of factors that pose a threat to farmers in the field consist of seasons (rainfall), rising input prices, outside family labor, pest and disease attacks. Then the strategy that can be applied to increase the income of lowland rice farmers in the study area is in quadrant IV is the Defensive Strategy (WT) which means the focus of the strategy that must be done by farmers is to optimize weaknesses to avoid various threats.